THE EFFECT OF PROBLEM BASED LEARNING MODEL ON RECOUNT TEXT WRITING SKILLS AT GRADE XI STUDENTS OF SMA SWASTA MERANTI (2025/2026) ACADEMIC YEAR - M. Rifaldi Lubis; Hamidah Sidabalok (Journal of Social and Economics Research, 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) model on students’ ability in writing recount texts of grade XI students at SMA Swasta Meranti in the 2025/2026 academic year. The method used in this research is a quantitative approach with an experimental design. The population of this study consisted of 51 students, and the sample was divided into two groups: the experimental group (XI-IPA) and the control group (XI-IPS). The experimental group was taught using the Problem Based Learning model, while the control group was taught using the conventional method. The data were collected through writing tests in the form of pre-test and post-test. The results showed that there was a significant improvement in students’ writing ability after the treatment. The mean score of the experimental group increased from 63.07 in the pre-test to 82 in the post-test, while the control group increased from 57.8 to 72.4. The data were analyzed using the t-test formula, and the result showed that the t-count value was higher than the t-table value at the significance level of 0.05. Based on the result of hypothesis testing, the alternative hypothesis (Hα) was accepted and the null hypothesis (Ho) was rejected. It means that the Problem Based Learning model has a significant effect on students’ writing recount text skills.